Designing a Project-Based Learning Model with Digital Technology Integration to Enhance Students’ Creativity in Craft Subject - Khaerudin Khaerudin; Eveline Siregar; Karimulloh Karimulloh (Universitas Sebelas Maret, 2026)
Project-Based Learning (PjBL) is increasingly recognized as a transformative approach in education, particularly for developing student creativity. Rather than focusing solely on conventional classroom routines, PjBL immerses learners in authentic, inquiry-driven, and collaborative projects that reflect real-world challenges. As digital technologies become increasingly central to daily life, educational models must innovate to meet the complex demands of the 21st century. This study set out to design and implement a technology-enhanced PjBL model for Grade VIII Craft (Prakarya) students at SMP Tahta Syajar, Bekasi, Indonesia. A quasi-experimental design was used, with 43 students divided into experimental and control groups. The intervention included digital brainstorming, visualization software, and collaborative platforms, all intended to scaffold the phases of project work. Student creativity was assessed using a validated, Torrance-based rubric measuring fluency, flexibility, originality, and elaboration. Results showed a significant improvement in all creativity domains for the experimental group (*p* < 0.05), with moderate to large effect sizes observed. Moreover, students reported greater enthusiasm, engagement, and creative confidence when digital technology was a core part of their learning.Overall, this study confirms that digital PjBL not only has a measurable positive impact on student creativity but also supports educational goals outlined by international frameworks such as OECD Education 2030 and UNESCO’s Futures of Education. The findings provide a foundation for future research in technology-supported creative learning.